PENGARUH PENDEKATAN KONTEKSTUAL BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN KONEKSI MATEMATIS DAN MOTIVASI BELAJAR SISWA - Robiatussalamah, Robiatussalamah; Sudin, Ali; Irawati, Riana (Jurnal Pena Ilmiah, 2019)
Indirectly, all the human activity are connected with mathematics. For example, if we doing economics activity in the market, we certainly do the counting like sum, diminution, multiplication, or division. Other than that, mathematics could be a facilitator on other various of scientific. Also mathematics could make a sistematic mindset on the brain for carry out their lives. Because of that, all human should be have mathematical connection skillsÂ  and also have big motivaion for learning mathematics. Since the old time, mathematics learned on school. The one of innovations of learning mathematic is ethnomatematics based contextual approach. The one of ethnomatematics is Cirebonâ€™s culture result is like â€œbatik motifâ€, traditional food, and traditional game. This study aims to know the differences in the increase in mathematical connection skills and student motivation on student who learn with ethnomatematical approaches and scientific approach, to know the differences in improving mathematical connection skills and learnig motivation trhrough an ethnomatematic based contextual approach and saintific approach, and to know the correlation between connection mathematics skills and learning motivation.This research used pretest-posttest control group design with samples of grade III SDN Grogol 1 dan SDN Dukuh 1 Cirebon. The results of this study are that there is an increase in N-Gain pretest and posttest scores on mathematical connection skills and learning motivation both of ethnomatematical based contextual approach and scientific approach. Conclusions of this research are: 1) the positive significanly effect of mathematical connection skills and learning motivation from ethnomatematics based contextal approaches, 2) the positive effect but not significantly increasing of mathematical connection skills and leraning motivation with scientific approach, 3) there is correlation between mathematical connection skills with learning motivation.